Susceptibility to erosion risks in soils dedicated to the pineapple cultivation in the state of Valle del Cauca, Colombia - Martinez López, Carolina; Rivera Paja, Albin Osvaldo; Menjivar Flores, Juan Carlos (Earth Sciences Research Journal, 2021)
In Colombia almost half of the soils are prone to erosion, where Valle del Cauca is one of the most affected departments with respect to its severity. In order to identify the susceptibility to erosion risks in terms of the rainfall erosivity and the incidence of the topographic factor in the main pineapple producing municipalities of the department, a study was carried out that contemplated the historical climatological information of more than 50 years, for which all available weather stations in the area were selected. The erosivity index (R–EI30), the modified Fournier index (MFI), and the topographic factor (LS) were estimated. The results indicate that the average MFI values ranged between (91.31 and 582.79) which correspond to the moderate, high and very high categories, the results of R-EI30 presented moderate, high, very high and extremely severe values (5076.91 MJ.mm.ha-1 - 22718.83 MJ.mm.ha-1), while the highest values of the topographic factor (with slopes up to 81°) coincide with the upper part of the river basin Dagua, predominantly in the municipality of Dagua. These values indicate that the soils in the area are susceptible to erosion risks depending on the rainfall erosivity and the topographic factor at a moderate, high and very high level, which can generate significant soil losses, and therefore they should be considered when establishing a pineapple crop.